2015
DOI: 10.1007/s10640-015-9876-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Internet and Mail Implementation of Stated-Preference Surveys While Controlling for Differences in Sample Frames

Abstract: The increasing use of internet surveys for stated preference studies raises questions about the effect of the survey mode on welfare estimates. A number of studies have conducted convergent validity investigations that compare the use of the internet with other survey implementation modes such as mail, telephone and in-person. All, but one, of these comparison studies is confounded different sample frames for the different modes of survey implementation. In this study we investigate differences in internet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 33 publications
0
28
2
Order By: Relevance
“…For instance, Windle and Rolfe [24] reported $70 per paper survey and $15 per online survey [24]. In contrast to previous studies in which lower (average ratio 0.76) [12] and similar WTP estimates were found [24,25] for online responders versus paper responders, we found some of the WTP estimates in our study to be slightly higher for online respondents than for paper respondents, whereas other WTP estimates were equal between the samples. This study was subject to limitations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For instance, Windle and Rolfe [24] reported $70 per paper survey and $15 per online survey [24]. In contrast to previous studies in which lower (average ratio 0.76) [12] and similar WTP estimates were found [24,25] for online responders versus paper responders, we found some of the WTP estimates in our study to be slightly higher for online respondents than for paper respondents, whereas other WTP estimates were equal between the samples. This study was subject to limitations.…”
Section: Discussioncontrasting
confidence: 99%
“…We are aware of one additional published study comparing paper with online DCE administration since this review. This study by Boyle et al [12] showed that Internetbased welfare estimates were 76% of the mail-based welfare estimates on average. The health-related study described in our article is a novel contribution to the already existing literature because we study mode effects using a large number of respondents drawn from the same sample frame (an Internet panel), who completed a nearly identical survey either online or on paper during the same period.…”
Section: Introductionmentioning
confidence: 92%
“…Concerns regarding the use of the internet-based methods for surveys revolve around issues of representation of the population given varying levels of computer literacy across age groups, varying degrees of connectivity to the internet across different sociodemographic or economic groups, and the extent to which respondents "take care" when answering the questionnaire. Lindhjem and Navrud (2011b) reviewed 17 SP studies in which comparisons between internet and other survey formats are made and found only minor differences in values (see also Boyle et al 2016;Sandorf, Aanesen, 32. Moreover, cell phone numbers cannot be as readily assigned to specific geographic areas, making it harder to match the respondent to their neighborhood's characteristics.…”
Section: Survey Mode and Samplingmentioning
confidence: 99%
“…Researchers must, however, be aware that using different modes (e.g. mail, Internet, interviews) to collect data can lead to variations in representativeness, convergent validity and data quality . The choice of survey mode will depend on the research question and population of interest and findings should be interpreted with mode effects in mind.…”
Section: Design and Analysis Of The Dcementioning
confidence: 99%